Pelaksanaan Restoratif Justice Terhadap Penyelesaian Perkara Tindak Pidana Kecelakaan Lalu Lintas Kepolisian Resor Indragiri Hilir - Alwi Radi Pria Sabra; Vivi Arfiani Siregar; Bambang Sasmita Adi Putra (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2026)
This study aims to analyze the implementation of restorative justice in resolving traffic accident criminal cases at the Indragiri Hilir Resort Police and to identify the obstacles encountered in its application. This research employs a sociological or empirical legal research method with a qualitative field approach. Data were collected through interviews, observations, and documentation studies, which were then analyzed descriptively and qualitatively. The results indicate that restorative justice is implemented through several stages, including report submission, investigation, criminal inquiry, mediation between the offender and the victim, achievement of a peace agreement, and case settlement in accordance with applicable regulations. The implementation reflects the principles of victim recovery, offender accountability, and active participation of the parties involved. The obstacles identified include internal factors such as administrative requirements and investigators' prudence, as well as external factors including differing interests of the parties, the offender's economic limitations, the victim's psychological condition, and the limited public understanding of restorative justice.